A study to determine the nutritional status of high school children in rural field practice area of medical college - Kurian, Joylyn; Mahesh, S. H.; Aravind, Akhil P.; Kurian, Jacqulin (International Journal of Contemporary Pediatrics, 2017)
Background: Overweight and underweight are major health problems among high school children worldwide. The present study was undertaken to determine the prevalence of overweight and underweight in Nagavalli Government High School children and to assess the various determinants associated with the two nutritional statuses. Methods: Cross-sectional study was carried out in government high school in Nagavalli by using preformed questionnaire. Totally 100 high school children from 8th, 9th and 10th standard were included in the study. Anthropometric measurements such as height, weight, body mass index, waist and hip ratio were assessed. Results: Majority of students was underweight. Only few students were overweight, and no cases of obesity were found, but some were found to have central obesity. The overweight students were mainly boys and the underweight were mainly girls. Nutritional values of the majority of students were poor due to unhealthy food lifestyles, lack of exercise, outdoor activities, imbalanced diet and inadequate food intake. Conclusions: 40% of female students were underweight as compared to 36% of male students who were underweight. Only 3% of girls were overweight compared to 4% boys who were overweight. In the present study, majority of high school students in 8th, 9th, and 10th standards were underweight, and the prevalence of overweight and obesity were less.